Anti‐tumor necrosis factor‐alpha therapy improves endothelial function and arterial stiffness in patients with moderate to severe psoriasis: A 6‐month prospective study. Issue 11 (7th April 2016) - Pina, Trinitario; Corrales, Alfonso; Lopez‐Mejias, Raquel; Armesto, Susana; Gonzalez‐Lopez, Marcos A.; Gómez‐Acebo, Ines; Ubilla, Begoña; Remuzgo‐Martínez, Sara; Gonzalez‐Vela, M. Carmen; Blanco, Ricardo; Hernández, Jose L.; Llorca, Javier; et al.
Abstract: The aim of the present study was to determine if the use of the anti‐tumor necrosis factor (TNF)‐α monoclonal antibody adalimumab could improve endothelial function and arterial stiffness in patients with moderate to severe psoriasis. This was a prospective study on a series of consecutive patients with moderate to severe psoriasis who completed 6 months of therapy with adalimumab. Patients with history of cardiovascular events, diabetes mellitus, kidney disease, hypertension or body mass index of 35 kg/m 2 or more were excluded. Assessment of endothelial function by brachial artery reactivity measuring flow‐mediated endothelial dependent vasodilatation (FMD%), and carotid arterial stiffness by pulse wave velocity (PWV) was performed at the onset of treatment (time 0) and at month 6. Twenty‐nine patients were studied. Anti‐TNF‐α adalimumab therapy yielded a significant improvement of endothelial function. The mean ± standard deviation (SD) FMD% values increased from 6.19 ± 2.44% at the onset of adalimumab to 7.46 ± 2.43% after 6 months of treatment with this biologic agent ( P = 0.008). Likewise, following the use of adalimumab, PWV levels decreased from 6.28 ± 1.04 m/s at the onset of adalimumab to 5.69 ± 1.31 m/s at 6 months ( P = 0.03). In conclusion, patients with moderate to severe psoriasis exhibit improvement of endothelial function and arterial stiffness following anti‐TNF‐α therapy. These findings are of potential relevance due to increased risk of cardiovascular disease in patients with severe psoriasis.